Pesantren as a Basis for Internalization of Pluralistic Values for Preparing a Democratic Citizens in a Diverse Society - Rohman, Abdul (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
Indonesia, as a pluralistic country, has potentialities of conflict at anytime as frequent violence has happened in Indonesia. Therefore, pluralism value has to be early introduced to the students in order to make them accustomed to a democratic attitude, and in turn, able to live in the diverse society harmoniously. Education has an important role to instill pluralism and tolerance values to students. It is a strategic way to socialize the values of tolerance, moderation, respect, and empathy, and to develop an attitude for learners in responding to the pluralism. This study will qualitatively discuss the role of pesantren in internalizing pluralism values to students in responding to a diverse society. It focuses on how the curriculum is constructed, instruction is done for the sake of creating a school culture for holding education that addresses pluralistic values. This study shows that pesantren with a pluralism based religious education is an effective basis for internalizing the values of pluralism to perform tolerance and inclusiveness to prepare the students to live in a pluralistic or diverse society.Indonesia, sebagai negara majemuk, memiliki potensi konflik yang bisa terjadi sewaktu-waktu dan hal ini bisa berujung pada kekerasan. Oleh karena itu, nilai pluralisme harus diperkenalkan lebih awal kepada siswa agar membuat mereka terbiasa dengan sikap demokratis, dan pada gilirannya, mampu hidup secara harmonis dalam masyarakat yang beragam. Pendidikan memiliki peran penting untuk menanamkan nilai pluralisme dan toleransi kepada siswa. Pendidikan merupakan media strategis untuk mensosialisasikan nilai toleransi, moderasi, rasa hormat, dan empati, dan untuk mengembangkan sikap bagi peserta didik dalam menanggapi pluralisme. Studi kualitatif ini akan membahas peran pesantren dalam menginternalisasikan nilai pluralisme kepada siswa dalam menanggapi masyarakat yang beragam. Studi difokuskan pada bagaimana kurikulum dibangun, pembelajaran dilakukan untuk menciptakan budaya sekolah dalam menyelenggarakan pendidikan yang membahas nilai-nilai pluralistik. Studi ini menunjukkan bahwa pesantren dengan pendidikan agama berbasis pluralisme merupakan dasar yang efektif untuk menginternalisasikan nilai-nilai pluralisme untuk memiliki sikap toleransi dan inklusivitas untuk mempersiapkan siswa hidup dalam masyarakat majemuk.